Group Identity in Public Deliberation - Marraud, Hubert (Informal Logic, 2023)
I argue that different argumentative practices require participants to categorize themselves in different modes. Accordingly, I distinguish four types of argumentation: rational argumentation, intergroup argumentation, intragroup argumentation, and, finally, personal argumentation. An inescapable implication of my approach to deliberation is that deliberation presupposes the self-categorization of participants in the same ingroup. Deliberation does not require, however, the group to antecede the deliberation process, and a distinctive feature of successful public deliberation is its capacity to produce social identification with the deliberative group. Thus, identity negotiation is an important part of deliberative processes.